STATE MANAGEMENT OF INNOVATION (INSTITUTIONAL ASPECTS) - Shepelenko E.G. (Pressing Problems of Public Administration, 2015)
The article deals with the main stages of theoretical and methodological understanding of the problems of innovative practices in terms of participation in innovative activities of various institutions, first of all, with institutions of the state policy. It is emphasized that market mechanisms without state regulation of the economy are not able to combine private business interests with the interests of society as a whole, have a positive impact on the harmonious sustainable development. Historical background of formation of state regulation of innovative processes is relevant at this stage of theoretical understanding of the role of the state as a social institution, the definition of effective mechanisms of state influence on the innovation processes.